Why people engage in parasuicide: a cross-cultural study of intentions. - Hjelmeland, H; Hawton, K; Nordvik, H; Bille-Brahe, U; De Leo, D; Fekete, S; Grad, O; Haring, C; Kerkhof, J; Lönnqvist, J; Michel, K; Renberg, E; et al. (2002)
Information obtained at interview from 1,646 parasuicide patients in 14 regions in 13 European countries participating in the WHO/EURO Multicentre Study on Suicidal Behaviour was used to study self-reported intentions involved in parasuicide. Comparisons were made across cultures, genders, and age groups. Although some statistically significant differences were found, the effect sizes were very small. The main finding from this study is thus that parasuicide patients in different countries tend to indicate that similar types of intentions are involved in their acts of parasuicide, and that the intentions do not vary greatly with gender or age. The hypothesis that rates of suicide and parasuicide vary between regions with the frequency with which suicidal intention is indicated by the patients was also tested, but was supported only for women and in relation to national suicide rates. The findings from this study are likely to be generalizable to other settings and have implications for clinical practice.